Developing a PMRI Learning Environment for Pre-Service Teachers to Teach Geometry in Elementary Education - Mulbasari, Anggria Septiani; Putri, Ratu Ilma Indra; Zulkardi; Nyimas Aisyah (Mathematics Education Journal, 2025)
There is a need for teachers to possess strong critical thinking skill and pedagogical skills. Unfortunately, many pre-service elementary teachers still struggle to develop these skills adequately, which can hinder the effectiveness of teaching and learning in the classroom. Therefore, this study aims to develop a valid, practical, and effective Pendidikan Matematika Realistik Indonesia (PMRI) learning environment to enhance the critical thinking and pedagogical abilities of pre-service elementary teachers. To achieve this aim, the study developed the Campus-Online-School (COS) model using a developmental research approach consisting of three phases: preliminary study, prototype development, and evaluation. Data were collected through observation, interviews, questionnaires, documentation, and tests, and analyzed using both qualitative and quantitative methods. The findings show that the developed learning environment is valid, practical, and effective in improving students’ critical thinking and pedagogical skills. Critical thinking was assessed through critical thinking test, while pedagogical ability was evaluated using Guskey’s framework. These findings offer important implications for teacher education, emphasizing the need to integrate comprehensive and contextual learning experiences to prepare future teachers who are reflective, adaptive, and equipped to face the challenges of modern classroom practice.